Behavioral activation for the control of depression in cancer patients: a review - Becerra Gálvez, Ana Leticia; Reynoso Erazo, Leonardo; Bravo González, María Cristina; Ordaz Carrillo, Maetzin Itzel (Psicooncología, 2017)
Behavioral activation (AC) is defined as a therapeutic process focused in increasing patient’s behaviors through an environment that provides the patient reinforcing contingencies. This therapy is empirically validated as a non-pharmacological treatment for depression because of its flexibility and its patient-tailored focus. The purpose of this work was to do a literature review about behavioral activation and major depressive disorder in cancer patients. We conducted a systematic review into seven databases using the PICO system in order to identify the articles. Studies in both English and Spanish published between 2000-2016 were included; the keywords “depression”, “behavioral activation therapy” and “cancer patients” were used in the search. 373 articles were found, however only 10 fulfilled the required criteria. The studies were carried out with non-hospitalized ambulatory patients; all the interventions were conducted individually. Results showed the relevance of behavioral activation as the main treatment of Major Depressive Disorder in an oncological population. We suggest to perform a clinical evaluation before applying AC considering: the tumor characteristics, clinical stage, type of treatment, collateral or adverse effects, cumulative toxicity and the natural story of the disease.
Keywords: Behavioral activation; depression; cancer